Drought Responses of Leaf Tissues from Wheat Cultivars of Differing Drought Tolerance at the Metabolite Level - Bowne, Jairus B.; Erwin, Tim A.; Juttner, Juan; Schnurbusch, Thorsten; Langridge, Peter; Bacic, Antony; Roessner, Ute (Molecular plant, 2012)
Drought has serious effects on the physiology of cereal crops. At the cellular and specifically the metabolite level, many individual compounds are increased to provide osmoprotective functions, prevent the dissociation of enzymes, and to decrease the number of reactive oxygen species present in the cell. We have used a targeted GC-MS approach to identify compounds that differ in three different cultivars of bread wheat characterized by different levels of tolerance to drought under drought stress （Kukri, intolerant; Excalibur and RAC875, tolerant）. Levels of amino acids, most notably proline, tryptophan, and the branched chain amino acids leucine, isoleucine, and valine were increased under drought stress in all cultivars. In the two tolerant cultivars, a small decrease in a large number of organic acids was also evident. Excalibur, a cultivar genotypically related to Kukri, showed a pattern of response that was more similar to Kukri under well-watered conditions. Under drought stress, Excalibur and RAC875 had a similar response; however, Excalibur did not have the same magnitude of response as RAC875. Here, the results are discussed in the context of previous work in physiological and proteomic analyses of these cultivars under drought stress.